Analysis of problems in the area of supply of inputs: case study company Fishcorp S.A. – Ecuador - Mera Vinces, Karina Elizabeth (SATHIRI, 2024)
The detection of problems, within the framework of engineering, is essential to assemble suitable improvement processes in a company. Undoubtedly, this action helps to prevent events that can damage the reputation and good institutional functioning. In Ecuador, there is the company Fishcorp S.A., a fish processor, which was the object of study through the application of an Ishikawa diagram, a non-participant observation and a Pareto diagram, merging a qualitative quantitative research methodology, of character non-experimental, inductive, that can be identified are the priority problems of the company and their possible origins and solutions. The lack of commitment, of organization and the insufficiency in the correct redistribution of  storage, are the most relevant findings in this study. It is evident that it is necessary to generate a clear labor organization chart, whose hierarchy is respected by its members, with a view to managing the supply and dispatch of inputs, during the production and logistics processes.
Keywords: Procurement; supplies; Pareto diagram; Lean; process